Pengaruh Motivasi Terhadap Kinerja Pegawai - Heru Sutapa (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2019)
Blood services through the UDD (Blood Donation Unit) PMI have been felt by the community so far. In this case the UDD PMI of Kediri City which consists of 20 employees is ready to help the community in the Kediri City in particular. Blood distribution is supported by employee performance where ERG motivation (Existence, Relatedness, Growth) is the variable that determines the performance of UDD PMI of Kediri City employees. This study employs the SPSS 16 program. Based on the results of this study, it can be seen the effect of the ERG motivation variable (Existence, Relatedness, Growth) on employee performance. Variables of existence needs influence employee performance, sig values 0,000 <0,05. Variable of social relations needs do not affect employee performance, sig value is 0.458> 0.05. Variable of growth needs affect employee performance, sig value 0.015 <0.05.